Formulation and Characterisation of a Hibiscus–Baobab-Based Functional Drink with Enhanced Nutritional and Antioxidant Properties - Pius M. Mathi (Editon Consortium Journal of Research in Medical and Health Sciences, 2026)
The purpose of this article is to develop a functional plant-based beverage that harnesses the nutritional and bioactive properties of baobab powder and hibiscus flower extract. A completely randomised design was used in the study, with baobab levels of 1 per cent, 2 per cent, and 3 per cent and hibiscus extract concentrations of 6.25 per cent, 12.5 per cent, and 25 per cent. A total of nine variants were evaluated for sensory, physicochemical, phytochemical, antioxidant activity, and nutritional attributes. Sensory evaluation was conducted by 25 untrained panellists familiar with ready-to-drink beverages using a 5-point hedonic scale. Analysis of variance (ANOVA) was conducted at a significance level of p ? 0.05. The hibiscus ratio of 12.5 per cent:1 per cent (HLB) recorded the highest sensory rating, particularly for overall acceptability (1.72). Subsequent analyses compared HLB with controls comprising a 2 per cent baobab drink and a 12.5 per cent hibiscus drink. The HLB formulation had a colour intensity of 136 Pfund and vitamin C content of 0.82 mg/g, while fructose levels did not differ significantly among the samples. No microbial growth was observed after culturing the drink. HLB contained the highest total phenolic content (47.51 mg GAE/100 g) and total flavonoid content (296.27 mg QE/100 g), alongside strong antioxidant activity, as reflected by the lowest DPPH IC50 value (10.32 mg/mL). Therefore, the 12.5 per cent:1 per cent formulation demonstrated favourable sensory acceptance, nutritional and antioxidant potential, and microbiological stability, highlighting its potential as a functional plant-based beverage.